English Game Website-Based Development for Fifth Grade Elementary School Students in First Semester - Mahadewi, Ni Made Nadindya; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu; Adnyayanti, Ni Luh Putu Era (Acitya: Journal of Teaching and Education, 2024)
Human life has entered the era of the Industrial Revolution 4.0, where technology plays an important role in human life. Likewise, teaching and learning activities are currently being collaborated with technology. However, in practice, many schools still tend to use conventional methods in teaching. Conventional methods This makes students tend to feel bored in participating in learning. Many learning methods have been developed which are considered effective in increasing student enthusiasm for learning. One of the effective, interactive, innovative, and attractive methods for students that can be used is the gamification method. This study aims to develop learning media in digital games for elementary school students learning English. The Design and Development (D&D) methodology and the ADDIE development model were used in this study. The subjects in this study were five fifth-grade elementary school students. Data collection methods in research are observation, interviews, and questionnaires. Furthermore, data analysis was carried out using descriptive qualitative and quantitative descriptive methods. The data obtained are (1) the results of the design and development of learning media using the ADDIE model (analysis, design, development, implementation, and evaluation). (2) results of product effectiveness and validity data from expert judgment, teachers, and users (students). Based on the results of expert judges, website game-based learning English media products are considered very valid as English learning media. Likewise, the English teacher and five fifth-grade students considered games very effective as learning media to increase learning motivation.